Contemporary public debates over history education - Nakou, Irene; Barca, Isabel (International review of history education ;, 2010)
The 6th book of the International Review of History Education Series, Contemporary public debates over history education, presents public debates on history education as they appear in 14 different areas of the world, in Asia, Europe, North and South America. In alphabetical order: in Brazil, by Maria Auxiliadora Schmidt and Tânia Braga Garcia, in Canada, by Peter Seixas, in England, by Rosalyn Ashby and Christopher Edwards, in Greece, by Irene Nakou and Eleni Apostolidou, in Israel, by Eyal Naveh, in Japan and South Korea, by Yonghee Suh and Makito Yurita, in Northern Ireland, by Alan McCully, in Portugal, by Isabel Barca, in Quebec (Canada), by Jean-Francois Cardin, in Singapore, by Suhaimi Afandi and Mark Baildon, in Spain, by Lis Cercadillo, in Turkey, by Dursun Dilek and Gülcin (Yapici) Dilek, and in the United States, by Peter Stearns.By illuminating common trends, national peculiarities and differences, this collective book further enriches our knowledge about crucial issues concerning public perspectives over history education in diverse parts of the world. It opens new questions and issues to be further investigated by all who are interested in this field, in terms of its historical, educational, global, national, ethnic, cultural, social and political dimensions in the current transitional and multicultural environment. This international dialogue therefore addresses historians, history education researchers, university professors, school teachers, policy makers, publishers, parents and all those who insist that history education is very important, especially if it enables young people to orientate in the present and the future in historical terms.